Reducing Production Lead Time Through Value Stream Mapping Approach - Yap, Ai Kin (2008)
The plastic injection molding has been widely used in the manufacturing industry due to its advance improvement in producing complex net shaped parts. However, there is still lack of efforts in the concept of early cost estimation on mold and most of the injection molders do not have adequate mechanisms to rapidly estimating the mold cost. This paper addresses the development of a method in estimating the cost of a plastic injection mold at the early stages of design. In this research, an early cost estimation formula for plastic injection mold had been developed from the ten sets of historical data of existing injection molds. This estimation formula had been tested with another four sets of molding part to check for its feasibility study. These all sample sets of injection molds were from a variety of part sizes and complexity designs from a local injection moldmaker. All tested molding parts were selected from the mold type of two-plate with cold runner system. The mold cost formula was derived from the part’s envelope volume, number of part dimensions, number of part actuators and part’s dimension tolerance as the mold cost independent variables. The strength of the relationships between the mold cost and its independent variables were investigated by using the statistical linear regression analysis. The results of analysis indicated that the number of part dimensions has the highest significant correlation with the mold cost, followed by the part’s envelope volume and then the number of part actuators, while the variable of dimension tolerance did not show a significant correlation to the mold cost.